What emotions do male prisoners experience in the lead-up to suicide and violence? A participatory visual method study - Hemming, Laura (The journal of forensic psychiatry & psychology, 2023)
Rates of suicide and violence are higher amongst male prisoners than the general population. This study aimed to explore the emotional experiences of male prisoners in the distal and immediate lead-up to acts of suicide and violence. Nine male prisoners created drawings of their emotions in the lead-up to an act of suicide and/or violence. Accompanying verbal interview data was collected to explore the narrative of these drawings. Polytextual thematic analysis was conducted on both the visual and audio data. Three themes were found. ‘The outside picture’ depicted the emotions that male prisoners exhibited externally. ‘The inside picture’ illustrated the internal emotions felt by male prisoners which were often complex and abstract. ‘The complexity of the picture’ denotes the complicated relationship between emotions and suicide/violence. Male prisoners experience a range of emotions in the lead up to acts of suicide and violence, with a similar set of emotions being experienced immediately prior to both suicide and violence. This study has illustrated the benefits of using a novel and creative methodology, and has demonstrated that future research with male prisoners could benefit from adopting a participatory visual methodology.